Colour and stability of the six common anthocyanidin 3-glucosides - Cabrita, Luís (2011)
This study on anthocyanin stability and colour variation (lambda max, absorptivity) in the pH range 1-12 during a period of 60 days storage at 10 and 23ºC, was conducted on the 3-glucosides of the six common anthocyanidins. It was mostly in the alkaline region that differences in colour and stability became significant. Although it has been generally accepted that anthocyanins are stable only at low pH values, this study revealed that, for some of the anthocyanin 3-glucosides (e.g. malvidin 3-glucoside), the bluish colours were rather intense and stability relatively high in the alkaline region. Thus, they can be regarded as potential colorants for some slightly alkaline food products.